2004
DOI: 10.1007/s00520-004-0598-1
|View full text |Cite
|
Sign up to set email alerts
|

Potential of chemotherapy?herb interactions in adult cancer patients

Abstract: Considerable potential exists for detrimental chemotherapy-HV interactions. Methods to improve communication of HV use between cancer patients receiving chemotherapy and health-care practitioners are necessary to identify and minimize the risk of these interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
119
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(128 citation statements)
references
References 32 publications
7
119
0
2
Order By: Relevance
“…Other reports show that melatonin, coenzyme Q10, green tea extract, cell forte (inositol and inositol hexaphosphate), glucosamine, peppermint, EPA (fish oil), and ginger are also popular dietary supplements/ natural products ( Fig. 1) [15,16].…”
Section: Worldwide Use Of Cammentioning
confidence: 99%
“…Other reports show that melatonin, coenzyme Q10, green tea extract, cell forte (inositol and inositol hexaphosphate), glucosamine, peppermint, EPA (fish oil), and ginger are also popular dietary supplements/ natural products ( Fig. 1) [15,16].…”
Section: Worldwide Use Of Cammentioning
confidence: 99%
“…Although, as a result of a lack of investigations, reports about clinically relevant pharmacokinetic (PK) interactions of CAM with chemotherapeutic drugs are scarce, it is expected that CAM-anticancer drug interactions contribute significantly to the interindividual variations in PK and clinical problems of unexpected toxicities and undertreatment seen in cancer patients. McCune et al [2] estimated that, of the population of patients taking chemotherapeutic drugs and CAM, at least 27% were at risk for developing clinically relevant CAM-drug interactions. It is therefore of utmost importance that treating oncologists are aware of the possibility and consequences of CAM-drug interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Herb-drug interactions, the form of adverse effect most often mentioned by oncologists, has been the subject of a number of reviews [38][39][40][41][42]. Despite these reviews and the concerns they raise, only two articles were identified that specifically tried to assess the degree of risk encountered by use of dietary supplements, including herbs, during cancer care [41,43].…”
Section: Risks Of Alternative Cancer Carementioning
confidence: 99%
“…Despite these reviews and the concerns they raise, only two articles were identified that specifically tried to assess the degree of risk encountered by use of dietary supplements, including herbs, during cancer care [41,43]. Of the 76 chemotherapy patients surveyed to identify potentially negative chemotherapy-herb or vitamin interactions, only three of the patients were using herbs (St. John's wort or Hypericum perforatumy and garlic or Allium sativum) that might have affected the metabolism of their chemotherapy.…”
Section: Risks Of Alternative Cancer Carementioning
confidence: 99%